The Influence of Public Relations Marketing on Social Media on Customer Loyalty of PT. Coda Payments Indonesia - Rahman, Tiara Nurul Rahman; Abraham, James; Widiyanto, Nursalina Rose (Ilomata International Journal of Social Science, 2025)
The rapid growth of the gaming industry in Southeast Asia has fueled the expansion of digital payment services, where Codashop by PT Coda Payments Indonesia plays a key role in facilitating seamless in-game transactions. Despite its active social media marketing public relations (MPR) efforts, Codashop faces challenges in social media engagement and customer loyalty compared to competitors. This research examines the extent to which MPR influences customer loyalty at Codashop. Through a quantitative correlational approach, data were collected from Codashop Indonesia's Facebook followers, who had completed multiple transactions. The findings indicate a strong positive relationship between MPR activities and customer loyalty. Regression analysis confirms that MPR significantly impacts customer retention, with events and media identity identified as the most influential components. Furthermore, customer advocacy through recommendations emerges as a key driver of loyalty. The study concludes that optimizing MPR strategies can strengthen customer relationships and enhance engagement, providing a competitive edge in the digital gaming industry. These insights emphasize the importance of strategic brand communication to build stronger customer connections. Companies like Codashop can leverage MPR more effectively to maintain loyalty, improve user engagement, and sustain competitive advantage in the evolving gaming market.